ANALISIS TINGKAT PELAYANAN RUAS JALAN SENTOSA-KEMAKMURAN-PELITA-LAMBUNG MANGKURAT-KH. AHMAD DAHLAN-BASUKI RAHMAT I KOTA SAMARINDA - AGUSTINA, SINTA (KURVA S JURNAL MAHASISWA, 2016)
One of the sector in effort develop one of the area is to develop build transportation fasilities and basic fasilities. Requirement of service activities and public transport will very affecting at its excelsior of ability number of is ownership of motor vehicle and also support by change of band road and public transport in town of Samarinda. Reffering to the increasing of hour at road street in town of Samarinda resulted progressively increasing it of is ownership of vehicle, and also the limited fund for development in sector of transportation land result not yet functioned decently operation of traffic facility which have been owned. From the calculation in road Sentosa – Kemakmuran – Pelita – Lambung Mangkurat - KH. Ahmad dahlan – Basuki Rahmat I result the level of service on the peak hours : on the roads Sentosa – Kemakmuran – Pelita, KH. Ahmad Dahlan and Basuki Rahmat I in the category D, where traffic is saturation and low speed, and roads Lambung Mangkurat in the category E, where traffic began to misfire and low speed. From the results that have been concluded, that the level of service roads Lambung Mangkurat Samarinda has been unable to serve vehicle passing the main influencing factors and should be addressed by enforcement of illegal parking as well restaurant and shops that takes the road.